Hydrothermal synthesis, characterization, and optical properties of wolframite ZnWO4 nanorods - Parada Siriwong (2018)
In this research, the effects of pH, reaction temperature and holding reaction time on the synthesis of one-dimensional ZnWO4 nanostructures by a hydrothermal method were studied. Phase, morphology and atomic vibration were characterized by X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM and TEM), and Fourier transform infrared (FTIR) and Raman spectroscopy. The pure monoclinic ZnWO4 structure was synthesized at the pH solutions of 7 and 8. By varying the pH values, the mixtures of monoclinic ZnWO4 and hexagonal ZnO as major and minor phases were detected at the pH 9 and 10 solutions, and the pure hexagonal ZnO phase at the pH 11 and 12. SEM and TEM images proved that ZnWO4 nanorods grew along the [021] direction, with the reaction temperature and time to control their morphologies. The Zn-O, Zn-O-W, and W-O stretching vibrations were detected at 474, 888, and 726 cm-1, and their corresponding bending vibrations at 430, 826, and 582 cm-1, respectively. The optical properties of ZnWO4 nanorods were also investigated by UV-visible (UV-vis) and photoluminescence (PL) spectroscopy. The above analyses proved that the appropriate condition for synthesizing of ZnWO4 nanorods is at pH 8 by the 200°C and 24 h hydrothermal treatment. © 2011 The Royal Society of Chemistry.